EFEKTIVITAS PENGAWASAN ATAS PEMBERIAN FASILITAS KEMUDAHAN IMPOR TUJUAN EKSPOR (KITE) PADA KANTOR WILAYAH DJBC BANTEN TAHUN 2021 S.D. 2023 - Moch Sentot Adi Prabowo; Ambarwati (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Trade is important for both individuals and a country. The development of information technology, communication, and transformation makes trading activities easier to the international level. In international trade, we recognize export activities. In an effort to increase export activities and support international trade activities, the Indonesian government through the Ministry of Finance provides KITE (Import Facility for Export Purpose) facilities to the perpetrators supervised by the Directorate General of Customs and Excise (DGCE). Supervision of the implementation of the KITE facility is by conducting monitoring and evaluation (Monev) activities by the DGCE Regional Office. This study aims to analyze the extent to which the effectiveness of supervision of the Banten DGCE Regional Office in carrying out its functions in monev activities for KITE facilities in the Banten region. This study analyzes the effectiveness of KITE facility supervision based on five aspects of indicators, namely the right policy, the right implementation, the right target, the right environment and the right process. Based on the results of interviews with the Banten DGCE Office, KITE facility recipients and academics, it can be concluded that all aspects of the indicator have been fulfilled by the Banten DGCE Office. However, behind the fulfillment of the indicator aspects there are still obstacles in the form of limited information technology systems in the supervision process, lack of human resources, non-optimal cross-agency coordination, and compliance from KITE facility companies. To overcome these obstacles, the Banten DGCE Regional Office has found solutions such as optimizing KITE facility supervision including strengthening digital systems, increasing employee capacity, routine coaching and education to facility recipient companies, and implementing risk-based supervision strategies and participatory approaches to build strategic partnerships and encourage voluntary compliance.